(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to assess the current status of solid waste management in Sabratha Municipality and propose a sustainable strategic plan for the period 2026-2031 using SWOT analysis, with a focus on reducing the carbon footprint resulting from the open dumping site. The study adopted a descriptive analytical approach. Data were collected through a questionnaire distributed to a stratified random sample of 195 residents using Cochran’s formula, in addition to semi-structured interviews with 5 officials and field observation of the dumpsite. The results revealed that the current waste management situation is very poor with an average satisfaction of 4.14/5, as waste accumulates in streets for more than 3 days and disposal relies entirely on an un sanitary open dump, causing high methane CH4 emissions and contributing to the municipality’s carbon footprint. SWOT analysis identified key strengths, notably 68.5% of residents are willing to sort waste at source and 47% are willing to pay for improved service, and weaknesses such as the absence of a strategic plan and complete dependence on the open dump. Based on the TOWS matrix, the study proposed four strategic objectives: launching the "Sabratha Sorts" community sorting project, closing the open dump and establishing a transfer station, reducing the carbon footprint by 30% through stopping open burning, and achieving 60% financial sustainability through a gradual service fee system. The study recommends the municipal council adopt the plan and apply for funding from UNDP/UNEP, while obligating the Libyan Center for Environmental Science and Technology Studies to monitor implementation.